Glucose and Lipid Profiles in Adolescents with Thalassemia Major and Its Association with Iron Overload in Specific Organs - Aryono Hendarto; Teny Tjitra Sari; Ludi Dhyani Rahmartani; Anggia Widyasari; Stephen Diah Iskandar (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Organ damage due to iron toxicity is one factor that increases the risk of getting cardiovascular and metabolic diseases in thalassemia patient. This study aims to determine glucose and lipid profiles in adolescents with thalassemia major and its association with iron overload in pancreas and liver.METHODS: This was a cross sectional study. Subjects were thalassemia major adolescents without any confounding factors that may affect glucose and lipid levels. Blood samples were collected to measure the glucose level, lipid profiles, ferritin level and transferrin saturation. T2-Magnetic Resonance Imaging was used to evaluate the iron overload in organs.RESULTS: From a total of 60 subjects, diabetes mellitus was diagnosed in 1 subject and impaired fasting glucose was diagnosed in 3 subjects. All subjects had high triglycerides/ high density lipoprotein-cholesterol (HDL-C) ratio, 59 subjects (98%) had low HDL-C, 18 subjects (30%) had hypertriglyceridemia, and none had abnormal high level of low density lipoprotein-cholesterol (LDL-C). The majority of subjects had ferritin ≥2,500 ng/mL (70%), mild pancreatic iron overload (56.6%), and moderate hepatic iron overload (43.8%). Degree of hyperferritinemia was not associated with glucose and lipid profiles. Blood glucose profiles were not associated with various degree of pancreatic iron overload. Similar result was also observed between lipid profiles and hepatic iron overload.CONCLUSION: Abnormal glucose and lipid profiles in thalassemia major can be found in adolescence. Normal blood glucose level isn’t necessarily associated with normal pancreatic iron deposition. Hepatic iron overload may worsen dyslipidemia in thalassemia major patients.KEYWORDS: glucose profile, lipid profile, pancreatic iron overload, hepatic iron overload, thalassemia major